Road Maintenance Practices in Nepal: A Case Study of Malekhu – Mugling Road Section - Dawadi, Archita; Shrestha, Santosh Kumar; Giri, Om Prakash (Advances in Engineering and Technology: An International Journal, 2022)
Road degradation is a major issue in Nepal due to main focus only on backlog maintenance and upgradation which evidently is an unsuccessful maintenance investment strategy worldwide. Considering global success of PBMC in time-cost-quality spectrum, it has been implemented in Nepal since 2003 but without success. Thus, ADB in 2016 revised PBM specifications and re-executed it, whose performance potential must be accessed with respect to current SMDP practice. The current study analyzes and compares effectiveness of SMDP and PBMC in terms of cost and quality for Malekhu- Mugling road section, and suggests a suitable maintenance practice in the current scenario of Nepal. This study reveals that strengthening SMDP practice shall be focused on before releasing a long term PBMC. The study concludes that the most suitable practice in terms of cost quality optimization is a strengthened SMDP as per PBMC standard whereby length worker perform PBMC standard routine, pavement and intervention based repairs due to their reliability during emergency. Then, one year contract shall be released incorporating two recurrent (prior and post monsoon) and a specific contract where contractors essentially follow performance based maintenance of roadside structures, traffic safety, pavement defects if any, and any emergency maintenance during monsoon. It is recommended that PBMC model shall be developed gradually from one year contract to multiyear contracts since there may be high chances of claims and conflicts in four year long PBMC.